Literature Review: Massage effleurage Terhadap Respon Nyeri Pada Ibu Bersalin Kala I Fase Aktif - Nining Sulistyowati (Jurnal Ilmu Kebidanan (Journal of Midwivery Science), 2021)
Most of the maternity mothers stated that they could not stand the pain they felt, especially in theabdomen, waist, back and radiating to the spine, so that the mother continued to feel pain during the firststage of labor. Contractions during labor can cause pain. Labor pain is a problem that has not receivedspecial attention, even though the purpose of intrapartum care itself is to reduce pain in labor, in additionto providing calm and comfort to the mother, it can also help speed up the process of opening the birthcanal. reduced by taking non-pharmacological actions, one of which is the provision of massageeffleurage. Massage effleurage which is done in the abdominal area to help reduce pain that arises duringthe labor process. The purpose of this study was to determine whether massage effleurage can reducethe pain response in women in the first stage of labor based on the literature review. The design ofscientific papers is in the form of a literature review with three articles taken from the Google Scholarjournal page with the keyword